Detection of Leishmania parasites in the testis of a dog affected by orchitis: case report - Manna Laura; Paciello Orlando; Morte Rossella; Gravino Angelo (Parasites & Vectors, 2012)
Abstract Background Transmission of canine leishmaniasis (CanL), a severe infection caused by L. infantum, usually occurs through the sand fly bite to the vertebrate host. A venereal route of transmission has also been suggested, but this issue is still controversial. Findings Here, we report a case of a dog affected by orchitis showing a clinical profile of L. infantum infection. By exploiting a real-time PCR assay, we detected a significantly higher DNA load of the parasite in the lymph node and testis than in blood and urine samples collected from the dog. Conclusions Our results suggest that: 1) L. infantum infection can be associated with testicular lesions in naturally infected dogs; 2) genital involvement could result in shedding of the parasites in the semen, favoring venereal transmission of the disease.